Indecent eco-theology: A case for practice-oriented eco-theology - Birkler, Margrethe Kamille (Dialog, 2023)
In this article, I propose that eco-theology should become indecent. Eco-theology has a lot to learn from Marcella Althaus-Reid's indecent theology and its orientation towards practice and warning against formalizing and intellectualizing theology within the universities’ walls. This focus on how we act in the world and then thereafter on how we understand the world, ourselves, and God can be advantageous for eco-theology as it tackles the very concrete reality of the climate crisis. In indecent theology, practice guides and corrects perception. After an introduction to Althaus-Reid's indecent theology and its relevance to the mobilization of religious communities in the climate crisis, I exemplify perception-oriented eco-theology with Sallie McFague's eco-theology and ask where a practice-oriented indecent eco-theology can find inspiration. I then offer a look into what an indecent eco-theology might look like and mention eco-friendly practices found in various religious communities.